Very-high-molecular-weight vs high-molecular-weight hyaluronic acid injections show long-term sustained benefits in the treatment of osteoarthritis of the knee: a 15-year Indian cohort study - Anish Kumar Aggarwal; Nakul Aggarwal; Jane Fitzpatrick (Journal of Cartilage & Joint Preservation)
Introduction: Lack of confidence in intra-articular hyaluronic acid injections for osteoarthritis (OA) may result from conflicting guidelines and pooling of results for different molecular weight products. Objectives: The objectives were to determine responder rates to injections of very-high-molecular-weight hyaluronic acid (VHMW-HA) vs high-molecular-weight hyaluronic acid (HMW-HA) for knee OA and treatment efficacy measured by the interval between follow-up injections. Methods: A retrospective analysis of a 15-year cohort from a single center. Inclusion criteria: adults with Kellgren-Lawrence Grade III or IV knee OA treated with hyaluronic acid injections. Subjects were stratified into 2 groups based on the molecular weight of the hyaluronic acid. Outcome measures were responder rates with improvement in Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores of >30% from baseline vs nonresponders; those with a response lasting >6 months after each injection were considered sustained responders. Results: In total, 2037 (female 1467 [72.02%] and male 570 [27.98%]) patients were treated. The overall primary responder rate was 73.44% (1496). VHMW-HA had significantly higher primary responders (75.21% vs 70.22%, P = .015) and significantly lower nonresponders (24.79% vs 29.78%, P = .015). As a subset of primary responders, the sustained responders had greater responses with VHMW-HA vs HMW-HA (85.54% vs 67.06%, P < .0001) and lower dropouts (14.46% vs 32.94%, P < .0001). The average interval between the first and the third injections was longer for VHMW-HA vs HMW-HA—5.67 vs 1.95 years (P < .0001). Conclusions: About 73.44% of subjects responded to treatment with intra-articular hyaluronic acid. The sustained response was greater in VHMW-HA vs HMW-HA and VHMW-HA has a longer duration of effect than HMW-HA.